Composite Risk Index for covid-19 from a geographic perspective: Costa Rica, March 2020 to May 2022. - Chamizo Garcia, Horacio Alejandro (2026)
An epidemiological, ecological, and territorial study was designed. Morbidity and mortality data between March 2020 and May 2022 were combined to build the district Composite Risk Index, from the geospatial perspective and with a focus on the Social Determinants of Health. Hot clusters of the Composite Risk Index (high risk) located in the Greater Metropolitan Area and cold (low risk) clusters were identified flanking or limiting. The increase in the average number of vaccines per inhabitant in one unit was associated with a 2% decrease in the ICR. The increase in the percentage of overcrowded housing, uninsured people, foreign-born people, population density, and the Social Development Index increased the ICR by 1% or 2%.  The ICR provides knowledge about the severity of the covid-19 epidemic, their behavior in geographical space is clearly differentiated, as well as the explanatory capacity of social determinants. Geographical proximity played a very important role in the covid-19 epidemic in Costa Rica.